(untitled) (Research, Society and Development, 2022)
The use of Open Educational Resources (OERs) for teaching health and sexuality in the science discipline of elementary school II. The present work briefly presents the theoretical foundation on the open access movement, open science allied to information and communication technologies, the work advances especially on open education and open educational resources and the potential of their use in the teaching and learning process in the school environment. The methodology included bibliographic research, which were read to understand the theme. The results that we can observe are that the repositories that deal with general disciplines and that on the specific topic of health and sexuality it was possible to map only the FIOCRUZ initiative through the EDUCARE repository. The research calls for further studies to understand how OERs can contribute more horizontally to science education.